A Pengembangan Booklet Digital Berbasis Gambar 3 Dimensi Pada Pembelajaran Biologi di SMA/MA: Literature Review - Sakinah, Shalmita; Fitri, Rahmadhani; Arsih, Fitri (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2023)
Students often experience difficulties in learning biology. This research aims to develop digital booklets based on 3D images in biology learning at SMA/MA as learning media to help students understand the material easily. Methods Research was conducted in a literature review using references from Google Scholar that were relevant to the research. There were 65 articles for development keywords and 10 articles for recapitulation data. The average validity results were in the very valid category. The validity test assesses the feasibility of a product, language, data presentation, and graphics. 3D-based digital booklets have met the requirements as media to be used in biology learning. The results show that the 3D-based digital booklets are the right solution for various problems, especially in biology learning at school. The benefits of development research are to increase the effectiveness of students in the learning process, provide convenience in accessing digital booklet media, and provide concise and systematic explanations that are easy to understand.